2019
DOI: 10.1101/613117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defective photosynthetic adaptation mechanism in winter restricts the introduction of overwintering plant to high latitudes

Abstract: Highlights: Introduced overwintering species exhibited lower capacity for photosynthetic CO 2 fixation and higher susceptibility for photoinhibition than native overwintering species during winter, which may limit their growth and survival.Abstract: Because of the need for agriculture and landscaping, many overwintering evergreen and biennial species that maintain green leaves over winter were introduced to higher latitudes. The green leaves of introduced overwintering species have to withstand a harsher winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Some studies have reported that the proportion of energy allocated to each energy-dissipated pathway is not constant under different environmental stresses [33]. Under low-temperature conditions, the light-harvesting complex (LHC) cannot completely utilize the absorbed light for CO 2 fixation [49]. NPQ is an important photoprotective mechanism that plays a role in protecting photosystem II (PSII) from damage under low-temperature conditions [16,46].…”
Section: Why Does the Gpp/sif Ratio Decrease At Low Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that the proportion of energy allocated to each energy-dissipated pathway is not constant under different environmental stresses [33]. Under low-temperature conditions, the light-harvesting complex (LHC) cannot completely utilize the absorbed light for CO 2 fixation [49]. NPQ is an important photoprotective mechanism that plays a role in protecting photosystem II (PSII) from damage under low-temperature conditions [16,46].…”
Section: Why Does the Gpp/sif Ratio Decrease At Low Temperaturesmentioning
confidence: 99%
“…Temperature has large effect on photosynthesis, and the effects of temperature on photosynthetic activities vary with the plant species [35,48]. The response of photosynthesis to low-growth-temperature conditions depends largely on the original distribution of the species [49]. Plants can be classified as species adapted to cold environmental conditions and species adapted to warm conditions (e.g., tropical or sub-tropical conditions).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, except for ENF, the effects of temperature on the SIF-GPP relationship in most plants have not been well-explored [31]. Furthermore, some studies have found that plant function types influenced SIF-GPP relationships and that the impacts of low temperatures on photosynthetic apparatuses of woody plants (for example, ENF) and herbaceous species (for example, winter wheat) may follow a different pattern during the winter [32]. Therefore, observations on winter wheat would represent an important contribution to our knowledge of the impact of the differences between SIF and GPP in response to temperature.…”
Section: Introductionmentioning
confidence: 99%